2009
DOI: 10.1007/s00247-009-1309-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT evaluation of total anomalous pulmonary venous connections: comparison with echocardiography

Abstract: MDCT can facilitate the diagnosis of TAPVC in certain cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…In a study by Oh et al, multidetector CT and echocardiography were compared in their ability to identify the drainage site of the common PV in TAPVC as well as to detect stenosis of the PVs and vertical vein [24]. Compared to their gold standard, direct detection at the time of surgery, the investigators found that echocardiography had a sensitivity of only 71% for identifying stenosis of the vertical vein in comparison to CT which had a sensitivity of 100% [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Oh et al, multidetector CT and echocardiography were compared in their ability to identify the drainage site of the common PV in TAPVC as well as to detect stenosis of the PVs and vertical vein [24]. Compared to their gold standard, direct detection at the time of surgery, the investigators found that echocardiography had a sensitivity of only 71% for identifying stenosis of the vertical vein in comparison to CT which had a sensitivity of 100% [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the infracardiac type is the most frequent (78%) [1], [3], [13], [14]. This type of TAPVR is characterized by obstruction located at the level of the diaphragm, caused by an extrinsic narrowing, resulting in a pulmonary edema appearance with normal cardiac silhouette in conventional imaging [1], [3], [6], [12].…”
Section: Discussionmentioning
confidence: 99%
“…Also, computed tomography allows for the performance of 3-dimensional reconstructions for advanced spatial and anatomic orientation [4], [6]. Reported sensitivities and specificities for MDCT for depicting the drainage site, areas of stenosis of the vertical vein, and the course and caliber of the anomalous vessel is 100% [4], [13]. As a disadvantage, MDCT uses ionizing radiation, which is why, in these patients, dose modulation must be adjusted to the neonatal body-weight parameters [4].…”
Section: Discussionmentioning
confidence: 99%
“…[137][138][139][140][141][142] Systemic venous anomalies are also well visualized by cardiovascular CT. [143][144][145] Cardiovascular CT has also been shown to accurately visualize congenital aortic anomalies including interrupted aortic arch and aortic coarctation in both pediatric and adult patients. [146][147][148][149][150][151][152][153] It is particularly useful for evaluation of the aortic arch after endovascular intervention (stent or stent graft) where aneurysm, aortic wall injury or recurrent arch obstruction are relatively common.…”
Section: Patientsmentioning
confidence: 97%